Erratum to: Leptogenesis in the Neutrino Option - Brivio, Ilaria; Moffat, K.; Pascoli, S.; Petcov, S. T.; Turner, J. (Journal of high energy physics, 2020)
The related work by Vedran Brdar, Alexander J. Helmboldt, Sho Iwamoto and Kai Schmitz.
Gesehen am 14.04.2020